2009
DOI: 10.1136/gut.2008.175497
|View full text |Cite
|
Sign up to set email alerts
|

Survival prediction of gastric cancer by a seven-microRNA signature

Abstract: Our seven-miRNA signature is closely associated with relapse-free and overall survival among patients with gastric cancer. The prognostic signature could be applicable to future decisions concerning treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
219
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(228 citation statements)
references
References 21 publications
3
219
1
4
Order By: Relevance
“…Previous studies have demonstrated that miR-30a is involved in the progression of various malignant tumors (20,21,23). However, the mechanism of miR-30a in the progression of cervical cancer remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that miR-30a is involved in the progression of various malignant tumors (20,21,23). However, the mechanism of miR-30a in the progression of cervical cancer remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that the dysregulation of miR-30a contributes to various malignant tumors, including lung, thyroid, gastric, breast and colon cancer (18)(19)(20)(21)(22)(23). miR-30a promotes tumorigenesis in these cancers by directly targeting tumor-associated proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Ueda et al reported the results of miRNA expression profiling in gastric cancer tissues and demonstrated that elevated levels of let-7 and miR-214 are associated with an unfavorable outcome (6). Li et al developed a seven-miRNA signature that functions as an independent predictor for relapse-free and overall survival in patients with gastric cancer (7).…”
Section: Introductionmentioning
confidence: 99%
“…miR-17-5p is part of the miR-17-92 polycistronic cluster, a family of oncogenic miRNAs (miR-17-5p, miR-17-3p, miR-18a, miR-19a, miR-20a, miR-19b-1 and miR-92-1) commonly deregulated in cancer, on chromosome 13 (16). It was previously reported that miR-17 is upregulated in colorectal (17)(18)(19), gastric (19,20) and pancreatic adenocarcinomas (19). A previous study demonstrated that miR-17-5p directly controls the expression of the type II transforming growth factor-β (TGF-β) receptor in colorectal cancer progression, inhibits the transcription of individual TGF-β responsive genes and indirectly stimulates angiogenesis through inhibition of a wide repertoire of anti-angiogenic factors (21).…”
Section: Discussionmentioning
confidence: 99%